Modeling FACTS Devices in Power System State Estimation - Seyyed Mehdi Mahaei; Mehrdad Tarafdar Hagh; Kazem Zare (International Journal of Electrical and Computer Engineering (IJECE), 2012)
In this paper is modeled different types of control devices including various kinds of FACTS devices based on power system states. Also, the impact of each device on the amount of injection active or reactive powers as well as active and reactive power flow will be investigated. Based on the type of these devices which can be in parallel, in series or in series–shunt in power systems, proposed models is considered differently. Accordingly, case studies will be performed for three different types of control devices installed in series, in shunt and in series-shunt fashions. State estimation results based on Weighted Least Square not only confirm the proposed models’ effectiveness in accurately state estimating of the system and measurement values but also shows that the estimated values can be obtained from the states of the control devices.Keywords: State Estimation; FACTS Devises; Measurement Function; WLS EstimatorDOI:http://dx.doi.org/10.11591/ijece.v2i1.132